Self-repairing hydrophobic coating and preparation method thereof

By using zirconium diboride, carbon nanotubes and other materials in the hydrophobic coating, combined with specific proportions and preparation methods, the problems of existing hydrophobic materials in environmental changes and durability are solved, and the self-repair of the coating is achieved and high hydrophobic performance, suitable for waterproofing, anti-corrosion, self-cleaning and other fields.

CN119286392APending Publication Date: 2025-01-10CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411572484.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing hydrophobic materials have unstable performance under different environmental conditions, and their durability decreases after long-term use, making it difficult to maintain their original hydrophobic properties.

Method used

Use a hydrophobic coating composed of zirconium diboride, carbon nanotubes, tetraethoxysilane, low-surface energy modifier, low-surface energy polymer, mesoporous silica, zeolite imidazole framework, etc., through specific The ratio and preparation method of the product form a hydrophobic coating with self-healing function.

Benefits of technology

It realizes the recovery of hydrophobic properties through a self-healing mechanism after the coating is damaged, improves the mechanical strength and stability of the coating, reduces the potential harm to the environment, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286392A_ABST
    Figure CN119286392A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing hydrophobic coating and a preparation method thereof, and belongs to the technical field of coating preparation, the hydrophobic coating comprises a main material and an auxiliary material, the main material comprises a mixture composed of zirconium diboride and carbon nanotubes; tetraethoxysilane is added; a low surface energy modifier, which is a low surface energy high-molecular polymer; mesoporous silica and a zeolite imidazole skeleton; the ingredients comprise deionized water, dimethylformamide, chloroform, tetrahydrofuran and tannic acid; the low surface energy modifier is composed of polydimethylsiloxane and 3-aminopropyltriethoxysilane, and the low surface energy high-molecular polymer is composed of polysilazane, a fluorine-containing polymer and a dendritic macromolecule. According to the hydrophobic coating, a pore channel structure is constructed in the hydrophobic coating, a mixture formed by mixing zirconium diboride and carbon nanotubes can store low-surface-energy substances, and when the surface of the coating cracks, the stored low-surface-energy substances can be activated and migrated to the surface of the coating through heating treatment, so that the self-repairing process is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating preparation, and in particular relates to a self-repairing hydrophobic coating and a preparation method thereof. Background Art

[0002] Superhydrophobic materials are materials that are extremely repellent to water. They have a special surface structure that prevents liquids from infiltrating their surface. They are usually composed of micro-nano rough structures and low surface energy chemicals. The research and application of superhydrophobic materials can be traced back to the observation of superhydrophobic phenomena in nature, such as the surface structures of organisms such as lotus leaves and water striders. The surfaces of these organisms are covered with micro-nano structures, forming a layer of air film that repels water molecules. Based on these observations, scientists have developed artificial superhydrophobic materials, which are widely used in medicine, construction, textiles, and military fields.

[0003] Although super-hydrophobic materials have many advantages, their application still faces problems of insufficient environmental adaptability and durability. The performance of commonly used hydrophobic materials on the market will change in different environments, the stability of the materials will be affected, and the long-term durability will be affected over time. Therefore, developing materials that can maintain stable performance under different environmental conditions and improving the long-term durability and stability of super-hydrophobic materials has become a new research direction for scientists. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a self-repairing hydrophobic coating and a preparation method thereof, so as to solve the problem that the performance of the existing hydrophobic coating rapidly decreases after being mechanically damaged.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a self-repairing hydrophobic coating, the hydrophobic coating comprising a main ingredient and ingredients, the main ingredient comprising: a mixture consisting of zirconium diboride and carbon nanotubes, tetraethoxysilane, a low surface energy modifier, a low surface energy high molecular polymer, mesoporous silica, and a zeolite imidazole framework; the ingredients are deionized water, dimethylformamide, chloroform, tetrahydrofuran, and tannic acid;

[0007] The low surface energy modifier consists of polydimethylsiloxane and 3-aminopropyltriethoxysilane, and the low surface energy high molecular polymer consists of polysilazane, fluorine-containing polymer and dendritic macromolecule.

[0008] Furthermore, the ratio of the main material to the auxiliary material is 6:4; by weight, 100-120 parts of a mixture consisting of zirconium diboride and carbon nanotubes, 55-65 parts of tetraethoxysilane, 38-42 parts of a low surface energy modifier, 35-45 parts of a low surface energy polymer, 38-42 parts of mesoporous silica, 40-46 parts of a zeolite imidazole framework; 150-180 parts of deionized water, 27-33 parts of dimethylformamide, 16-20 parts of chloroform and 16-20 parts of tetrahydrofuran, and 18-22 parts of tannic acid.

[0009] Furthermore, in parts by weight, 110 parts of a mixture consisting of zirconium diboride and carbon nanotubes, 60 parts of tetraethoxysilane, 40 parts of a low surface energy modifier, 55 parts of a low surface energy polymer, 40 parts of mesoporous silica, 43 parts of a zeolite imidazole framework; 50 parts of deionized water, 30 parts of dimethylformamide, 18 parts of chloroform and 18 parts of tetrahydrofuran, and 20 parts of tannic acid.

[0010] Furthermore, the particle size of the carbon nanotubes is 10-20 microns.

[0011] Furthermore, a method for preparing a self-repairing hydrophobic coating comprises the following steps:

[0012] S1, after mixing zirconium diboride and carbon nanotubes evenly, add them into deionized water and stir evenly, then add low surface energy modifier and low surface energy high molecular polymer and stir to obtain a first mixture, and let it stand;

[0013] S2, adding tetraethoxysilane, mesoporous silica, and zeolite imidazole framework to the remaining deionized water, stirring evenly to obtain a second mixture, and letting it stand;

[0014] S3, mixing the first mixture and the second mixture and stirring for 30 minutes, then adding the remaining deionized water, dimethylformamide, chloroform, tetrahydrofuran, and tannic acid, ultrasonically dispersing and mixing, and then standing;

[0015] S4, after filtering, a hydrophobic coating is obtained;

[0016] S5. Apply the hydrophobic coating to the surface of the substrate, and dry it at 38-45° C. to obtain a hydrophobic coating.

[0017] Furthermore, the standing time of the first mixture is 2h30min-3h30min; the standing time of the second mixture is 1h-2h; and the standing time after adding the ingredients is 2h-3h.

[0018] Furthermore, the step S1 and step S2 are performed at 30-40° C.; and the step S3 is performed at room temperature.

[0019] Furthermore, in step S4, the filtration mesh size is between 4 and 6 meshes; and the drying time is not less than 3 hours.

[0020] The beneficial effects of the present invention are:

[0021] 1. The hydrophobic coating prepared by the present invention has a pore structure constructed inside. The mixture of zirconium diboride and carbon nanotubes can store low surface energy substances. When the coating surface cracks, the stored low surface energy substances will be activated and migrate to the coating surface through simple heating treatment, realizing a self-repair process.

[0022] 2. The mesoporous silica used in the present invention has a pore structure that can carry repair agents such as tannic acid, dimethylformamide, chloroform and tetrahydrofuran, providing space for the flow and storage of the repair agent, so that the repair agent can be released in time for self-repair when the coating is damaged.

[0023] 3. The tetraethoxysilane used in the present invention is used as a binder in the preparation process, and can also be used for siliconization treatment of metal surfaces to improve the light transmittance of optical glass.

[0024] 4. The coating prepared by the present invention has excellent hydrophobic properties: the combined effect of low surface energy substances and high molecular polymers makes the coating extremely hydrophobic; it also has a self-repairing function: the pore structure and nano-storage groove structure inside the coating enable the coating to restore its hydrophobic properties through a self-repairing process after being damaged; it also has good mechanical strength: the addition of zirconium diboride and carbon nanotubes significantly improves the mechanical strength of the coating, enabling it to withstand greater external forces; it is also environmentally friendly: the use of fluorine-free materials reduces potential harm to the environment.

[0025] 5. The hydrophobic coating prepared by the present invention successfully achieves the self-repairing performance of the coating by optimizing the raw material selection and preparation process, while maintaining excellent hydrophobic properties and mechanical strength. The coating has broad application prospects in the fields of waterproofing, anti-corrosion, and self-cleaning.

[0026] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to make the purpose, technical solution and beneficial effects of the invention clearer, the present invention provides the following drawings for illustration:

[0028] Figure 1 The present invention is a flow chart for preparing the coating. DETAILED DESCRIPTION

[0029] A self-repairing hydrophobic coating and preparation method thereof:

[0030] Example 1

[0031] S1, after 55 parts of zirconium diboride and 55 parts of carbon nanotubes are mixed evenly, they are added to 50 parts of deionized water and stirred evenly, and then 55 parts of low surface energy modifier and 40 parts of low surface energy polymer are added and stirred to obtain a first mixture, and the mixture is allowed to stand for 3 hours;

[0032] S2, adding 55 parts of tetraethoxysilane, 40 parts of mesoporous silica, and 43 parts of zeolite imidazole framework to 50 parts of deionized water, stirring evenly to obtain a second mixture, and standing for 1h30min;

[0033] S3, mixing the first mixture and the second mixture for 30 minutes, then adding 50 parts of deionized water, 30 parts of dimethylformamide, 18 parts of chloroform, 18 parts of tetrahydrofuran, and 20 parts of tannic acid, ultrasonically dispersing and mixing evenly, and then standing for 2h30min;

[0034] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0035] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a hydrophobic coating.

[0036] Example 2

[0037] S1. After 70 parts of zirconium diboride and 45 parts of carbon nanotubes are mixed evenly, they are added to 55 parts of deionized water and stirred evenly, and then 42 parts of low surface energy modifier and 35 parts of low surface energy polymer are added and stirred to obtain a first mixture, and the mixture is allowed to stand for 3 hours;

[0038] S2, adding 65 parts of tetraethoxysilane, 42 parts of mesoporous silica, and 40 parts of zeolite imidazole framework to 55 parts of deionized water, stirring evenly to obtain a second mixture, and standing for 1h30min;

[0039] S3, the first mixture and the second mixture were mixed and stirred for 30 minutes, and then 55 parts of deionized water, 27 parts of dimethylformamide, 20 parts of chloroform, 16 parts of tetrahydrofuran, and 22 parts of tannic acid were added, and the mixture was evenly dispersed by ultrasonic dispersion, and then allowed to stand for 2h30min;

[0040] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0041] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a hydrophobic coating.

[0042] Example 3

[0043] S1. After 50 parts of zirconium diboride and 65 parts of carbon nanotubes are mixed evenly, they are added to 55 parts of deionized water and stirred evenly, and then 38 parts of low surface energy modifier and 45 parts of low surface energy polymer are added and stirred to obtain a first mixture, and the mixture is allowed to stand for 3 hours;

[0044] S2, adding 55 parts of tetraethoxysilane, 38 parts of mesoporous silica, and 46 parts of zeolite imidazole framework to 55 parts of deionized water, stirring evenly to obtain a second mixture, and standing for 1h30min;

[0045] S3, the first mixture and the second mixture were mixed and stirred for 30 minutes, and then 55 parts of deionized water, 33 parts of dimethylformamide, 16 parts of chloroform, 20 parts of tetrahydrofuran, and 18 parts of tannic acid were added, and the mixture was evenly dispersed by ultrasonic dispersion, and then allowed to stand for 2h30min;

[0046] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0047] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a hydrophobic coating.

[0048] The difference between Example 2 and Example 3 and Example 1 is that the number of parts of each raw material is different, but all are within the protection scope of the present invention. In order to verify the superiority of the raw materials, proportions and methods of the present invention, comparative examples 1 to 4 are set here.

[0049] Comparative Example 1

[0050] S1. Add 120 parts of zirconium diboride to 50 parts of deionized water and stir well, then add 20 parts of low surface energy modifier and 100 parts of low surface energy polymer and stir to obtain a first mixture, and let stand for 3 hours;

[0051] S2, adding 25 parts of tetraethoxysilane, 100 parts of mesoporous silica, and 10 parts of zeolite imidazole framework to 50 parts of deionized water, stirring evenly to obtain a second mixture, and standing for 1h30min;

[0052] S3, mixing the first mixture and the second mixture for 30 minutes, then adding 50 parts of deionized water, 10 parts of dimethylformamide, 40 parts of chloroform, 40 parts of tetrahydrofuran, and 5 parts of tannic acid, ultrasonically dispersing and mixing evenly, and then standing for 2h30min;

[0053] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0054] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a coating.

[0055] The difference between Comparative Example 1 and Example 1 is that zirconium diboride is not added, and the ratio of each raw material is not within the protection scope of the present invention. The prepared coating has poor hydrophobic properties and low bonding strength, and cannot achieve the purpose of the present invention.

[0056] Comparative Example 2

[0057] S1, after 55 parts of zirconium diboride and 55 parts of carbon nanotubes are mixed evenly, they are added to 50 parts of deionized water and stirred evenly, and then 55 parts of low surface energy modifier and 40 parts of low surface energy polymer are added and stirred to obtain a first mixture, and the mixture is allowed to stand for 3 hours;

[0058] S2, adding 55 parts of tetraethoxysilane, 40 parts of mesoporous silica, and 43 parts of zeolite imidazole framework to 50 parts of deionized water, stirring evenly to obtain a second mixture, and standing for 1h30min;

[0059] S3, mixing the first mixture and the second mixture and stirring for 30 minutes;

[0060] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0061] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a coating.

[0062] The difference between Comparative Example 2 and Example 1 is that no auxiliary materials are added, and the obtained coating has almost no hydrophobicity, and cannot achieve the purpose of the present invention.

[0063] Comparative Example 3

[0064] S1, after mixing 55 parts of zirconium diboride and 55 parts of carbon nanotubes evenly, add them into 50 parts of deionized water and stir evenly to obtain a first mixture, and let it stand for 3 hours;

[0065] S2, adding 55 parts of tetraethoxysilane to 50 parts of deionized water, stirring evenly to obtain a second mixture, and letting it stand for 1h30min;

[0066] S3, mixing the first mixture and the second mixture for 30 minutes, then adding 50 parts of deionized water, 30 parts of dimethylformamide, 18 parts of chloroform, 18 parts of tetrahydrofuran, and 20 parts of tannic acid, ultrasonically dispersing and mixing evenly, and then standing for 2h30min;

[0067] S4, filter the paint 3 times using a 5-mesh screen, with an interval of 15 minutes between each pass;

[0068] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a coating.

[0069] The difference between Comparative Example 3 and Example 1 is that the low surface energy modifier, low surface energy polymer, mesoporous silica and zeolite imidazole skeleton are not added to the main ingredients, and the obtained coating has poor repair function and very general hydrophobic properties, which cannot achieve the purpose of the present invention.

[0070] Comparative Example 4

[0071] S1. Add 55 parts of zirconium diboride, 55 parts of carbon nanotubes, 55 parts of low surface energy modifier, 40 parts of low surface energy polymer, 55 parts of tetraethoxysilane, 40 parts of mesoporous silica, and 43 parts of zeolite imidazole framework to 120 parts of deionized water; S3. Filter the coating three times with a 5-mesh screen, each time with an interval of 15 minutes;

[0072] S5. Apply the coating to the surface of the substrate with a scraper and dry at 40° C. for 4 hours to obtain a coating.

[0073] The difference between Comparative Example 3 and Example 1 is that the preparation method of the present invention is not adopted, and all raw materials are directly added at one time, so that each raw material fails to react fully, and the obtained hydrophobic coating has poor performance and cannot achieve the purpose of the present invention.

[0074] The coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were scraped onto the surface of a substrate of the same texture, placed in the same open air environment, and left to stand for 15 days, during which the surface of the coating was naturally damaged. After 15 days, the changes in the coating surface were observed. The results are shown in the following table:

[0075]

[0076] It can be seen from the above table that the hydrophobic coating prepared by the method, raw material and proportion of the present invention is scraped on the substrate surface and cured under low temperature conditions. The raw material in the coating undergoes a cross-linking reaction to form a stable structure, and has excellent hydrophobic properties. After being naturally destroyed, it can also be self-repaired, effectively reducing the cost of scraping again, and saving resources. And Comparative Example 1-Comparative Example 4, due to the fact that the method, raw material and proportion of the present invention are not adopted, it is incomplete to obtain coating performance, and there is no hydrophobic property, and self-repair can not be effectively performed, and the purpose of the present invention cannot be achieved.

[0077] The hydrophobic coating with self-repairing function prepared by the present invention successfully achieves the self-repairing performance of the coating by optimizing the raw material selection and preparation process, while maintaining excellent hydrophobicity and mechanical strength. The coating has broad application prospects in the fields of waterproofing, anti-corrosion, self-cleaning, etc.

[0078] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A self-repairing hydrophobic coating, characterized in that: The hydrophobic coating comprises a main material and ingredients, wherein the main material comprises: a mixture of zirconium diboride and carbon nanotubes, tetraethoxysilane, a low surface energy modifier, a low surface energy high molecular polymer, mesoporous silica, and a zeolite imidazole framework; and the ingredients are deionized water, dimethylformamide, chloroform, tetrahydrofuran, and tannic acid; The low surface energy modifier consists of polydimethylsiloxane and 3-aminopropyltriethoxysilane, and the low surface energy high molecular polymer consists of polysilazane, fluorine-containing polymer and dendritic macromolecule.

2. A self-repairing hydrophobic coating according to claim 1, characterized in that: The ratio of the main material to the auxiliary material is 6:4; by weight, 100-120 parts of a mixture consisting of zirconium diboride and carbon nanotubes, 55-65 parts of tetraethoxysilane, 38-42 parts of a low surface energy modifier, 35-45 parts of a low surface energy high molecular polymer, 38-42 parts of mesoporous silica, 40-46 parts of a zeolite imidazole framework; 150-180 parts of deionized water, 27-33 parts of dimethylformamide, 16-20 parts of chloroform and 16-20 parts of tetrahydrofuran, and 18-22 parts of tannic acid.

3. The self-repairing hydrophobic coating according to claim 1, characterized in that: By weight, 110 parts of a mixture consisting of zirconium diboride and carbon nanotubes, 60 parts of tetraethoxysilane, 40 parts of a low surface energy modifier, 55 parts of a low surface energy high molecular polymer, 40 parts of mesoporous silica, 43 parts of a zeolite imidazole framework; 50 parts of deionized water, 30 parts of dimethylformamide, 18 parts of chloroform and 18 parts of tetrahydrofuran, and 20 parts of tannic acid.

4. A self-repairing hydrophobic coating according to claim 3, characterized in that: The particle size of the carbon nanotubes is 10-20 microns.

5. A self-repairing hydrophobic coating according to any one of claims 1 to 4, further comprising a method for preparing the self-repairing hydrophobic coating, characterized in that: The following steps are included: S1, after mixing zirconium diboride and carbon nanotubes evenly, add them into deionized water and stir evenly, then add low surface energy modifier and low surface energy high molecular polymer and stir to obtain a first mixture, and let it stand; S2, adding tetraethoxysilane, mesoporous silica, and zeolite imidazole framework to the remaining deionized water, stirring evenly to obtain a second mixture, and letting it stand; S3, mixing the first mixture and the second mixture and stirring for 30 minutes, then adding the remaining deionized water, dimethylformamide, chloroform, tetrahydrofuran, and tannic acid, ultrasonically dispersing and mixing, and then standing; S4, after filtering, a hydrophobic coating is obtained; S5. Apply the hydrophobic coating to the surface of the substrate, and dry it at 38-45° C. to obtain a hydrophobic coating.

6. A method for preparing a self-repairable hydrophobic coating according to claim 5, characterized in that: The first mixture is allowed to stand for 2h30min-3h30min; the second mixture is allowed to stand for 1h-2h; and the standing time after adding the ingredients is 2h-3h.

7. The method for preparing a self-repairable hydrophobic coating according to claim 5, characterized in that: The steps S1 and S2 are performed at 30-40° C.; the step S3 is performed at room temperature.

8. The method for preparing a self-repairing hydrophobic coating according to claim 5, characterized in that: In step S4, the filtration mesh size is between 4 and 6 meshes; and the drying time is not less than 3 hours.

Citation Information

Patent Citations

  • Preparation method of self-repair super-hydrophobic polyurethane coating

    CN103449736A

  • Superhydrophobic composite coating with self-repair function and preparation method thereof

    CN105038439A

  • Preparation method of epoxy resin microcapsule with self-repairing function

    CN110975773A

  • Intelligent coating with double functions of corrosion repair and early-stage corrosion early warning as well as preparation method and application of intelligent coating

    CN116948506A